1989
DOI: 10.1007/bf00505181
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a cohort of diabetic patients

Abstract: In a prospective study of mortality in a large group of Scottish diabetic patients, ischaemic heart disease was responsible for 51% of deaths, with the diabetic relative risks of death being 3.8, 2.7 and 2.2 for the age groups 45-64, 65-74, and 75 years and over, respectively. The diabetic relative risks for mortality from all causes were 5.5, 2.3, 1.7, 1.3 for age ranges 15-44, 45-64, 65-74, and 75 and over, respectively. The all cancer mortality rate is not reduced in diabetic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 7 publications
7
40
0
Order By: Relevance
“…Better sensitivity was reported in studies with smaller (n ϭ Ͻ550) sample sizes (4,14,16,19,20,24,27,28,31) and limited to patients with diabetes (4,14,16,19,31). Studies outside the U.S. tended to report higher sensitivity (51-70%), but differences in diabetes diagnostic criteria and procedures for completion of death certificates make comparisons difficult (13,14,16,28,31,33,34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Better sensitivity was reported in studies with smaller (n ϭ Ͻ550) sample sizes (4,14,16,19,20,24,27,28,31) and limited to patients with diabetes (4,14,16,19,31). Studies outside the U.S. tended to report higher sensitivity (51-70%), but differences in diabetes diagnostic criteria and procedures for completion of death certificates make comparisons difficult (13,14,16,28,31,33,34).…”
Section: Discussionmentioning
confidence: 96%
“…The few previous longitudinal studies of diabetes reporting on death certificates were conducted in foreign countries, making comparisons with U.S. data difficult (13)(14)(15)(16), were based on data collected before 1994 (17,18), or were from diabetic populations only (4). In these studies the correct reporting of diabetes on death certificates ranged from 35 to 65%.…”
mentioning
confidence: 99%
“…Other limitations of this study are the under-recording of diabetes. Regarding the declaration of diabetes in health interview surveys, some studies have concluded that educational differences in misreporting of diabetes are small or absent [25]. Moreover, health surveys of diabetes only report diagnosed diabetes, which only represents between 30% and 50% of total diabetes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…HTN is a major cause of mortality in both type 1 and type 2 diabetics [37,38]. The prevalence of HTN appears to be about 2-folds more in patients with diabetes in contrast to non-diabetic patients, with this relationship being clearer in type 1 DM [39].…”
Section: Hypertensionmentioning
confidence: 99%